ANALISIS EKONOMI USAHATANI PADI ORGANIK DI KABUPATEN SRAGEN - Widowati, Endang - (Jurnal Ilmu Ekonomi dan Pembangunan, 2006)
This research will explain variabels which farmers need to make decision on choosing the system of rice cropping. The writer will analys the factors which have influenced the rice production in Sragen Regency. It also will know the differences between the profit of organic and non organic farming. The object of this research will focus to organic and non organic farming. Stratified random sampling has been used to collect data from 20 subdistricts in Sragen Regency. The writer has collected 4 group of rice farming for each subdistricts.??????????? The writer has used descriptive analysis to describe characteristics of farmer with chi-square analysis. Regression analysis has used to analys factors which have influenced the rice production in Sragen Regency. To analys the differences between the income of organic and non organic farming, the writer has used statistics analysis.??????????? The result shows that land, asset, labour, seed cost, fertilizer cost, and system of rice cropping have influenced the income of farming. Based on statistic analysis, this result have found the differences between organic and non organic farming?Keywords: organic farming, non organic farming, regression analysis